Theories of Functional Pragmatics (Eurasian Journal of Philology Science and Education, 2020)
The article considers a new direction in linguistics functional pragmatics. Functional pragmatics is an integrated theory of language that considers the language of a person in society.In the theory of functional pragmatics its speech fields and categories are being pooled. This article discusses their types and describes the characteristics of them. Functional pragmatics as a new direction in linguistics analyzes discourses and texts. Today, the analysis of texts and discourse on this theory makes it possible to explore any language. Empirical methods and theoretical materials of functional pragmatics are very relevant.The basic category of functional pragmatics are speech actions. The article discusses the term procedure, which is the minimum unit of speech action. Until now, this term has been used frequently in medical science. Despite this procedure, how the term has its own characteristic in linguistics. The rest of the article describes the internal structures of speech action as a speech act, illocutionary act and. etc. The illocutionary act and its types are especially described. Since discourses and texts are speech acts, examples from literary texts are given during the analysis of speech fields. That will allow us to understand the types of speech fields of functionalpragmatics.Functional pragmatics has imperial research methods that are conducted through the HIAT program. Such future research will help develop artificial intelligence and deeply understand, explore any languages.